Aeration to Improve Biogas Production by Recalcitrant Feedstock - John Loughrin (Environments, 2019)
Digestion of wastes to produce biogas is complicated by poor degradation of feedstocks. Research has shown that waste digestion can be enhanced by the addition of low levels of aeration without harming the microbes responsible for methane production. This research has been done at small scales and without provision to retain the aeration in the digestate. In this paper, low levels of aeration were provided to poultry litter slurry through a sub-surface manifold that retained air in the sludge. Digestate (133 L) was supplied 0, 200, 800, or 2000 mL/day air in 200 mL increments throughout the day via a manifold with a volume of 380 mL. Digesters were fed 400 g of poultry litter once weekly until day 84 and then 600 g thereafter. Aeration at 200 and 800 mL/day increased biogas production by 14 and 73% compared to anaerobic digestion while aeration at 2000 mL/day decreased biogas production by 19%. Biogas quality was similar in all digesters albeit carbon dioxide and methane were lowest in the 2000 mL/day treatment. Increasing feed to 600 g/week decreased gas production without affecting biogas quality. Degradation of wood disks placed within the digesters was enhanced by aeration.